Divided fates the state, race, and Korean immigrants' adaptation in Japan and the United States - Suzuki, Kazuko 1967- (Lexington Books, 2016)
"This book takes a cross-national and comparative approach, beyond American models, to examine how members of a single ethnic group adapt differently to distinct host societies. In her study of Korean immigrants to Japan and the United States, Suzuki finds that the state's mode of reception and its racialization of migrants determine adaptation patterns"--Provided by publisher.